Ionospheric disturbance dynamo associated to a coronal hole: Case study of 5–10 April 2010. Issue 5 (28th May 2014) - Fathy, I.; Amory‐Mazaudier, C.; Fathy, A.; Mahrous, A. M.; Yumoto, K.; Ghamry, E.
Abstract In this paper we study the planetary magnetic disturbance during the magnetic storm occurring on 5 April 2010 associated with high‐speed solar wind stream due to a coronal hole following a coronal mass ejection. We separate the magnetic disturbance associated to the ionospheric disturbance dynamo (Ddyn) from the magnetic disturbance associated to the prompt penetration of magnetospheric electric field (DP2). This event exhibits different responses of ionospheric disturbance dynamo in the different longitude sectors (European‐African, Asian, and American). The strongest effect is observed in the European‐African sector. The Ddyn disturbance reduces the amplitude of the daytime H component at low latitudes during four consecutive days in agreement with the Blanc and Richmond's model of ionospheric disturbance dynamo. The amplitude of Ddyn decreased with time during the 4 days. We discuss its diverse worldwide effects. The observed signature of magnetic disturbance process in specific longitude sector is strongly dependent on which Earth's side faces the magnetic storms (i.e., there is a different response depending on which longitude sector is at noon when the SSC hits). Finally, we determined an average period of 22 h for Ddyn using wavelet analysis.